Nontuberculous Mycobacterial Pulmonary Disease. Issue 1 (January 2015) - Cowman, Steven; Loebinger, Michael
<x xml:space="preserve">Abstract</x> Nontuberculous mycobacteria (NTM) are a group of ubiquitous environmental organisms which may cause infection in humans, most commonly pulmonary disease. Most individuals with disease have an underlying structural lung disease such as bronchiectasis or chronic obstructive pulmonary disease; however, individuals with no known risk factors may also develop disease; the reason for this is unknown. NTM are frequent contaminants of clinical samples, and diagnosis does not rest upon culture alone, but also clinical and radiographic findings. The clinical course of patients with NTM is variable, patients may remain stable without treatment and the decision to treat may not be straightforward. Treatment for NTM varies between species but is usually with multiple antimycobacterial agents for a prolonged period of time; surgery may also be employed in selected cases. Drug intolerance is common and outcomes for many species are inferior to those seen in tuberculosis. The prognosis of NTM infection is poor, although this may also reflect the poor underlying health of the affected patients. There is a need for the development of better treatment regimens and for research aimed at understanding the mechanisms leading to disease susceptibility and progression.